Kegiatan pembelajaran sebagai upaya dalam menstimulus perkembangan sosial-emosional anak usia dini - Aghnaita Aghnaita; Ajeng Almira Salsabila; Camelia Hanik; Maulida Syafitri; Norhayani Norhayani; Normiati Normiati; Riatul Nadia (Aṭfāluna: Journal of Islamic Early Childhood Education, 2020)
This study aims to determine the emotional social development of early childhood in Integrated Early Childhood Education Tarbiyatul Athfal UIN Antasari Banjarmasin as well as the form of learning activities undertaken as an effort to stimulate the emotional social development. The research method used is qualitative research on 6 children and learning activities that can stimulate children's emotional emotional development as primary data. Based on research conducted, the results obtained that the child's emotional social development tends to be unstable. Children often prefer to play alone. Nevertheless, children also begin to show interest in hanging out in the surrounding environment and doing play activities together. In addition, there are several factors influence, such as: social emotional experiences of children, gender differences, differences in family and cultural backgrounds, and parenting. While the form of learning activities that are pursued in the form of stimulation of children's emotional social development include: routine activities of reading Asmaul Husna and short surahs, filling in journals, playing indoor, and conducting learning activities. The activity was carried out through exemplary methods, sharing learning, and collaborative games.